Kinetics and mechanism of alkaline hydrolysis of N-(o aminophenyl)phthalimide in the presence and absence of cationic micelles and sodium salts of aliphatic acids - Ahmad, Wan Hamdah Wan; Fagge, Ibrahim Isah; Sim, Yoke Leng; Khan, Mohammad Niyaz (Science Reviews 2000, 2018)
Pseudo first-order rate constants, kobs, for the alkaline hydrolysis of N-(o-aminophenyl) phthalimide, obtained at constant [CTABr]T (total concentration of cetyltrimethylammonium bromide) and varying concentrations of inert salt MX (MX = sodium formate, sodium acetate, sodium propanoate, sodium butyrate, sodium valerate and sodium hexanoate) follow the relationship: kobs (K0 + θKX/S [MX])/(1 + KX/S [MX]) where θ and KX/S are empirical constants and S = HO-. The values of KX/S for each aliphatic acid decrease with an increase in [CTABr]T. This relationship gives an empirical constant whose magnitude is the measure of the ability of an ion, X- X/S, to expel another counterion S-, from the cationic micellar surface to the bulk aqueous phase. The values of the empirical constant, K X/S, are used to derive the ion exchange constant, KBr X.